Study of the epidemiological and serological aspects of toxoplasmosis in pregnant women and newborns treated in the city of Blumenau, Santa Catarina, Brazil - Sgrott, Mateus Augusto; Dassoler Puff, Stefano Giorgio; Zaniboni Siqueira, Keila; Araújo Greinert Goulart, Juliane (Revista de Patologia Tropical / Journal of Tropical Pathology, 2024)
Toxoplasmosis is a disease caused by the protozoan parasite Toxoplasma gondii, with greater relevance in developing countries, capable of leading to serious complications in pregnant women and immunocompromised patients. Gestational toxoplasmosis, in most cases, occurs when a woman acquires a primary T. gondii infection during pregnancy, posing a risk of fetal sequelae or even fetal death, the disease being of compulsory notification in Brazil. The objectives of this study were to assess the epidemiological status of gestational and congenital toxoplasmosis in the city of Blumenau/SC and to increase knowledge about its prevalence in the region. To achieve this, an analysis of city data recorded in the Blumenau/SC Epidemiological Surveillance Service database was conducted between the years 2019 to 2021. During the study period, the city of Blumenau presented lower prevalence of gestational toxoplasmosis (2.93/1,000 pregnant women) and congenital toxoplasmosis (2.31/10,000 live births) than other regions of Brazil. Proper adherence to prenatal care and its screening protocols, as well as the early initiation of treatment, can result in a low incidence of congenital infections even in tropical areas with high seroprevalence. Rapid and accessible immunoglobulin G avidity testing allows for the exclusion of suspected cases without the need for invasive tests or unnecessary treatments. Education, on the other hand, plays a crucial role in disease prevention and should focus on encouraging proper prenatal care and providing adequate information about the disease. Finally, treatment adherence should be monitored and promoted. KEY WORDS: Pregnancy complications; infectious; public health; toxoplasmosis, congenital; toxoplasmosis; epidemiology.